(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
During several field work campaigns to the Karakorum Mountains samples containing Devonian macrofossils were collected by M. Gaetani and P. Le Fort, mostly in the uppermost Yarkhun Valley (Northern Pakistan). Generally, Devonian rocks are outcropping rather extensively in several thrust sheets of the Northern Karakorum Terrain, namely in the Chillinji, Baroghil/Lashkargaz, and the Karambar Units. The dolostones of the Tash Kupruk Zone, similar to the Chilmarabad Fm. of the previous units, are also Devonian in age. Fossils mentioned below originate from measured logs (Yarkhun River, Chillinji, Ribat), others from isolated localities. Identification of most of the fossils on species, or even at genus-level is difficult due to their moderate to poor state of preservation. Recrystallisation phenomena that had affected particularly porous skeletons, especially those with small-sized intra-skeletal cavities (i.e. intra-tabular spaces of small-sized tabulate corallites, and inter-laminar spaces of stromatoporoid skeletons) often preclude reliable determination. Nevertheless, from the following formations tabulate corals and calcareous green-algae could be determined: Chilmarabad Fm. (Lashkargaz/Baroghil Unit,), Shogram Fm. (Yarkhun River section), Margach Fm. (Ribat section), the Tash Kupruk dolostones (loose blocks north of Inkip). The taxa described are Pseudopalaeoporella ? sp., Receptaculites cf. chardini, Pachyfavosites polymorphus, Thamnopora grandis, Thamnopora cf. longdongshuiensis, Thamnopora cf. reticulata, Celechopora devonica, Alveolites (Alveolites) hudlestoni, Heliolites ? sp., Pachycanalicula ? sp., "Caunopora", and Helicosalpix asturiana. Most of the fossils described point to Middle to Upper Givetian age, although they are not particularly age diagnostic.